FRG and GDR The state of the nation's external economy - Manfred Holthus (Intereconomics, 1971)
With its “Report on the State of the Nation 1971” the Government of the Federal Republic of Germany (FRG) simultaneously presented an extensive volume of collected studies. Drawn up by 50 experts, the report on the development in the two German states should contribute to facilitating political judgement and to sobering political discussion, according to Willy Brandt The author participated in the composition of the chapter dealing with the economic integration of the two German states with their specific allies. This paper is a summary of his report.
Keywords: 330; Germany